Treatment outcome in children with non-syndromic unilateral cleft lip and palate based on congenital and postnatal treatment factors: a multi-population study using threedimensional digital models - Haque, Sanjida Haque (2020)
This cross-sectional study aimed to evaluate dental arch relationship (DAR) and maxillary arch dimension (MAD) of non-syndromic unilateral cleft lip and palate (UCLP) children and to explore the congenital (gender, UCLP type, UCLP side, family history of cleft, family history of Class III malocclusion) and postnatal treatment (types of cheiloplasty and palatoplasty) factors that affect the treatment outcome of UCLP children using laser scanned three-dimensional digital models (LS3DM). Furthermore, the present study evaluated and compared the mesiodistal (MD) tooth sizes on cleft side (CS) and non-cleft side (NCS) of the maxilla among male and female UCLP children using LS3DM as well as evaluated the association among gender and races. Two hundred and fifty-five pretreatment orthodontic plaster dental casts of UCLP children from Malaysia, Bangladesh, and Pakistan populations, 85 from each were selected into this study. The mean age was 7.69± 2.46 (mean± SD). All the dental casts were scanned and converted into LS3DM by Next Engine laser scanner (Santa Monica, USA). DAR was assessed by two raters using GOSLON Yardstick (GY) and EUROCRAN index (EI) and modified Huddart Bodenham (mHB) scoring system. Inter-canine width (ICW), inter-molar width (IMW), arch depth (AD) and MD dimensions of the tooth were measured with Mimics software (Belgium). Treatment outcome was rated into two groups; favourable and unfavourable groups based on GY, EI and mHB scoring systems. Kappa statistics used to evaluate the intra- and interexaminer agreements and logistic regression analysis (LRA) used to explore the responsible factor that affect DAR. The intra-class correlation was used to evaluate the intra- and inter-examiner agreements and multiple linear regression analyses used to evaluate the association between multiple factors and MAD (ICW, IMW, and AD) and MD dimension of tooth size of the maxilla. p-value was set at 5%. The mean GY score was 2.97, 3.40 and 3.09 in Malaysia, Bangladesh and Pakistan population respectively. Unfavourable DAR was significantly associated with Bardach technique (BT) of palatoplasty (p = 0.03) in Malaysian, male UCLP subjects (p = 0.03), modified Millard technique (MMT) of cheiloplasty (p = 0.04) and BT of palatoplasty (p = 0.04) in Bangladeshi and BT of palatoplasty (p = 0.04) in Pakistani population using GY. The mean EUROCRAN scores were 3.07 and 2.21 in Malaysia, 2.66 and 2.07 in Bangladesh and 2.56 and 2.07 in Pakistan for DAR and palatal morphology (PM) respectively. Using LRA, unfavourable DAR was significantly associated with positive family history of cleft (p = 0.03) and BT of palatoplasty (p < 0.001) in Malaysian, MMT of cheiloplasty (p = 0.010) and BT of palatoplasty (p = 0.02) in Bangladeshi and left sided UCLP (p = 0.03), MMT of cheiloplasty (p = 0.02) and BT of palatoplasty (p = 0.04) in Pakistani population using EI. The total mHB score was -9.98, -8.76 and -6.57 in Malaysia, Bangladesh and Pakistan population respectively. Using LRA, unfavourable DAR was significantly associated with positive family history of cleft (p = 0.02 and p = 0.04) and BT of palatoplasty (p = 0.03 and p = 0.01) in Malaysian and Bangladeshi population respectively, and BT of palatoplasty (p < 0.001) in Pakistani population. The mean dimension of ICW was 26.88 mm, 26.61 mm and 26.69 mm and IMW was 45.24 mm, 42.89 mm and 43.33 mm and AD was 29.81 mm, 29.06 mm and 27.06 mm in Malaysians, Bangladeshis and Pakistanis respectively. Significant association was observed between narrower ICW and MMT of cheiloplasty (p < 0.001) in Malaysian and BT of palatoplasty (p = 0.04 and p = 0.02) in Malaysian and Bangladeshi population respectively. Significant association was observed between shorter AD and complete type of UCLP (p = 0.01) in Bangladeshi. Regarding tooth size asymmetry, significant difference observed in MD dimension of all the teeth size of CS and NCS of maxillae among male and female in all populations. This multi-population study suggested that treatment outcome based on DAR and MAD of non-syndromic Malaysians, Bangladeshis and Pakistanis UCLP children was significantly correlated with some of congenital and postnatal treatment factors using LS3DM. The study also revealed significantly smaller teeth size in CS compare to NCS in relation to gender, and races in all populations using LS3DM.